Cognitive reserve and coping strategies predict the level of perceived stress during COVID-19 pandemic: A cross-sectional study. (September 2022) - Panico, Francesco; Luciano, Sharon Mara; Sagliano, Laura; Santangelo, Gabriella; Trojano, Luigi
Abstract: The COVID-19 pandemic and the measures to avert contagion heavily impacted individuals' mental health. In the present cross-sectional study, we investigate the relationship between cognitive reserve, coping modalities and the perceived stress during a chronic stage of COVID-19 pandemic by online administration of three standardized questionnaires in a sample of healthy volunteers covering a large lifespan (18–85 years). We found that positive orientation to problems and higher levels of cognitive reserve were associated with lower levels of stress. Conversely, coping strategies involving negation, substance consumption, and appeal to other people and religion to face everyday life, together with higher education, were associated with higher levels of stress. These results shade light on the long-term psychological consequences of COVID-19 and call for the development of psychological interventions improving coping and cognitive reserve, to preserve and restore mental health following the pandemic.